Determinantes del riesgo percibido y de la confianza inicial en el líder de un equipo de trabajo. Incidencia del entorno de trabajo y los rasgos del líder - Guinalíu Blasco, Miguel (2013)
Aspects such as the growing importance of teamwork and the emergence of new organizational schemes based on information and communication technologies highlight the need for understanding the mechanisms that promote effective leadership. In this sense, this paper analyzes the determinants of perceived risk and trust on a team leader. The research consists of two experiments. The first analyzes the influence of working environment—virtual or traditional—on the two dependent variables considered. The second experiment focuses on the virtual environment and analyzes the importance of the inclusion of a photo on the electronic leader’s profile in order to generate trust. Moreover, it analyzes the impact of perceived leader traits (attractive or expert) on the ability to build trust and the perception of risk. It shouldbe noted that these analyzes are contextualized in the initial stage of team development, poorly studied in the literature. Among others, the results reveal the greater difficulty of building trust in virtual environments, as well as the relevance of including graphical information on the profile and that the leader with expert traits has the greatest potential to buildtrust. These results have interesting managerial implications, which are discussed along with the main future research lines and limitations.